Fish, Fetishization, and Faith in the Arctic Ocean - Marion Grau; Lovisa Mienna Sjöberg (Religions, 2024)
The ocean is a site of energy, space, movement, depth, and extraction. The biblical creation account begins there, with the energy of movement of the Spirit over the Deep. The exploitation of the ocean can be read as a desecration of the Deep, of divine presence and creativity, where beings of the deep roam. Many of these beings are beyond human knowledge, known only to the Creator. Many disturbances of the ocean floor and ocean dwellers have already occurred; penetrating even deeper into the ocean is a form of sacrilege. Extractive politics in the Arctic Ocean and in Northern Sápmi continue following decades of overfishing, poaching, and repression of indigenous coastal traditions. The Sámi tradition and ecological theologies offer a different way of looking at coastal and ocean regions. As tools to counter the calls for endless extraction, we offer narratives that highlight the importance of the coastal Sámi oral tradition and a decolonial ecotheology of a protective apophasis of the Deep. Countering extraction involves rejecting a hermeneutics of commodity fetish that distorts the ocean and those that live and travel within it by framing them as endlessly extractable. This article seeks to resist the extraction of oceanic waters and remind us of ways to respect ocean-dwelling species, the ocean, and ourselves in a time where we are facing the sixth great extinction.